Cadmium(1−x)zinc(x)telluride thin films deposited by sequential pulsed laser deposition. (September 2015) - Hernandez-Como, N.; Elizalde, J.; Mejia, I.; Quevedo-Lopez, M.A.
Abstract: In this work, sequential pulsed laser deposition was used for the deposition of cadmium zinc telluride (CZT) thin films. CZT is a ternary II–VI compound semiconductor with a tunable band gap between 1.51 and 2.26 eV. In this work, three different CZT film compositions were achieved at room temperature by sequential deposition of nanometric layers with a precise number of laser shots on the cadmium telluride (CdTe) and zinc telluride (ZnTe) targets. XPS, XRD and UV–vis transmittance techniques were used to characterize the CZT films. The atomic content of zinc ranged from 60% down to 13%. This represents an enlargement of the lattice constant from 6.19 to 6.41 Å, and a band gap decrement from 1.94 to 1.55 eV. In addition, the CZT film resistivity can be modulated between the CdTe (4.1×10 7  Ω-cm) and ZnTe (2.8×10 5  Ω-cm) values. Our results demonstrated that the sequential pulsed laser deposition can be used to obtain several CZT film compositions with precise control of its stoichiometry and can be extended to the production of other ternary compounds.